Changes in the prevalence of chronic conditions associated with abdominal obesity between 1999 and 2014. Issue 1 (9th December 2019) - Randhawa, Arshdeep K.; Ardern, Chris I.; Kuk, Jennifer L.
Summary: To examine the trends in chronic conditions after accounting for temporal differences in body mass index (BMI) and waist circumference (WC). Pooled cycles (1999‐2014) of the U.S. National Health and Nutrition Examination Survey (NHANES) were analysed (n = 36 959). The models were adjusted for caloric intake, smoking, medications use and physical activity. The prevalence of diabetes increased in women with general or abdominal obesity (BMI*time; WC*time, P  < .05), but there were no differences in men. For hypertension, independent of BMI, the prevalence was not different over time in both sexes ( P  > .05), whereas for a given WC, there was a decrease in the prevalence over time in women (WC*time, P = .05). For dyslipidemia, independent of BMI, the prevalence decreased in men, whereas for a given WC, there was a decrease in the prevalence in both sexes ( P  < .05). Over the same time frame, blood pressure, low‐density lipoprotein and triglycerides decreased, while plasma glucose increased independent of general and abdominal obesity ( P  < .001). The relationship between obesity and chronic conditions has changed over time. There may be other changes that have altered how obesity is related with metabolic health markers over time. Further investigation is needed to better understand the current causes of chronic conditions.